Dampak Sosial-Ekonomi Koperasi Difabel dan Perwujudan Microfinance Access - Nopiah, Ririn; Islami, Puji Amalia (INKLUSI, 2018)
Microfinance is a financial institution that can be reached by various groups of people, such as disabled groups. Microfinance programs provide access to financial services to people with disabilities in the form of savings and credit. People with disabilities need financial services to improve their economic and social levels. However, in general, existing microfinance has not fully reached the disabled groups. This study aims to describe the implementation of activities and the role of the Self-Reliance Savings and Loans Cooperative (KSP BANK) for the disabled in Yogyakarta. The analysis used in the study is the analysis of Paired T-test with SPSS 16.0 analysis tools. This study shows that the level of social-economic of mermbers with disability has a positive and significant increase after the operation of KSP BANK Difabel for the members with disabilities. [Keuangan mikro merupakan lembaga keuangan yang dapat dijangkau oleh berbagai kelompok masyarakat, seperti kelompok difabel. Program keuangan mikro memberikan akses jasa keuangan kepada difabel baik dalam bentuk tabungan maupun kredit. Layanan jasa keuangan sangat dibutuhkan difabel dalam meningkatkan taraf ekonomi-sosial mereka. Akan tetapi, pada umumnya keuangan mikro yang ada belum menjangkau secara penuh kelompok difabel. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan kegiatan dan peran Koperasi Simpan Pinjam (KSP) Bangun Akses Kemandirian (BANK) Difabel Yogyakarta. Analisis yang digunakan dalam penelitian adalah analisis uji Paired T-test dengan alat analisis SPSS 16.0. Penelitian ini menunjukkan bahwa Taraf ekonomi-sosial difabel mengalami peningkatan positif dan signifikan setelah adanya koperasi difabel bagi anggota KSP BANK Difabel tersebut.]